5-aminolevulinic Acid and Surgical Margin Analysis in Calvarial Metastasis with Pericranium or Dural Extension: Technical Note - da Silva Junior, Erasmo Barros; Silva, Joseph Franklin Chenisz da; Coelho Neto, Maurício; Cavalcanti, Marcella Santos; Ramina, Ricardo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2020)
Metastasis to the calvarium with direct pericranium or dural infiltration may be treated with radical surgical removal in selected cases. We describe microsurgical resection of calvarial metastases with fluorescence-guided technique using 5-aminolevulinic acid (5-ALA) in two female patients with breast cancer. Fluorescence findings were positive in both cases. Margins in the scalp and dural layer were 5-ALA negative at the end of surgical removal. Intraoperative pathology was performed in all cases to confirm if oncological limits were free of disease. One case was 5-ALA positive in the outer layer of the dura-mater and another in the pericranium. At the end of the removal in both cases, the surgical margins were 5-ALA fluorescence-free. Intraoperative pathology confirmed oncological limits of the resection. 5-aminolevulinic acid fluorescence-guided surgery for calvarial metastases with pericranium and/or dural extension seems to be a safe and reliable method to aid the surgical margins for complete removal, possibly delaying or avoiding adjuvant irradiation for progression control.
Keywords: 5-aminolevulinic acid; calvarial metastases; fluorescence surgery; metastases; skull metastases; surgical margins